1991
DOI: 10.1111/j.1467-6486.1991.tb00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Strategic Planning Systems in Large Organizations: A Contingency Approach*

Abstract: This study investigates the relationship among four design parameters of planning systems and five different firm and environmental characteristics. The impact of this multivariate relationship on organizational effectiveness is then examined using a sample of 115 large manufacturing firms. The findings show general support for the proposition that, in order to be effective, a strategic planning system should be designed in such a way that the specific situational setting of the firm is reflected in the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 30 publications
5
86
0
2
Order By: Relevance
“…As complexity increased, charismatic leaders seemed to prefer the pragmatic situation to either the ideological or charismatic situation. This finding is consistent with Mumford (2006), Kukalis (1991), andPlumlee (2003) who suggested that vision formation may prove difficult in ambiguous conditions. At first glance, this pattern is somewhat contradictory with the findings of Bedell-Avers et al (in press) that seemed to suggest charismatic leaders preferred less-structured conditions.…”
Section: General Findingssupporting
confidence: 82%
See 2 more Smart Citations
“…As complexity increased, charismatic leaders seemed to prefer the pragmatic situation to either the ideological or charismatic situation. This finding is consistent with Mumford (2006), Kukalis (1991), andPlumlee (2003) who suggested that vision formation may prove difficult in ambiguous conditions. At first glance, this pattern is somewhat contradictory with the findings of Bedell-Avers et al (in press) that seemed to suggest charismatic leaders preferred less-structured conditions.…”
Section: General Findingssupporting
confidence: 82%
“…As noted earlier, it may be difficult for a charismatic leader to form a future-oriented vision in highly complex conditions (Kukalis, 1991;Plumlee, 2003). In these highly complex conditions, however, charismatic leaders may be adequate problem-solvers if, indeed, asked to be (i.e., placed into a pragmatic situation).…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…(Hickson et al, 1986;Kukalis, 1991). In fact, as the IT organization found, such 'out of the box' behavior is unlikely unless it is carefully orchestrated.…”
Section: Implementation: Diagnosing the Issuesmentioning
confidence: 99%
“…More recent studies provide findings that show that strategic planning does indeed result in a superior performance particularly in dynamic environments . Several studies propose that firms operating in environmentally complex and uncertain environments tend to put more emphasis on rational decision-making processes such as strategic planning Bourgeois and Eisenhardt, 1988;Kukalis, 1991).…”
mentioning
confidence: 99%